DIAMETER DISTRIBUTION PROJECTIONS IN MIXED OMBROPHYLOUS FOREST IN THE CENTER-SOUTH REGION OF PARANA, BRAZIL - Monteiro, Fabio Gomes; Retslaff, Fabiane Aparecida de Souza; Figueiredo Filho, Afonso (Floresta, 2022)
Projection techniques of the diametric structure, such as Transition Matrix and Movement Ratio, have been frequently used in Araucaria Forest, but there is no information about the potential of the Wahlenberg method. In addition, studies on the subject hardly had enough data to assess projections with observed data. Thus, the objective herein was to evaluate the Transition Matrix, Movement Ratio and Wahlenberg Methods in projecting the diametric structure in a Mixed Ombrophylous Forest in the Center-South region of Paraná, Brazil, and compare the projections with observed data. The study was carried out with data from 25 permanent plots of one hectare each, installed in the National Forest of Irati. The measurements of these plots occurred every three years, from 2002 to 2017, covering 15 years of monitoring. The database applied to the three methods used measurements from two periods: three years (2002-2005) and six years (2002-2008). With this, the projections were made for multiple periods, which enabled comparing them with the observed data. The accuracy of the generated projections was assessed by the Kolmogorov-Smirnov test and the Reynolds Index. It was observed that there was a reduction tendency in the projection of the total number of trees in the forest for the three tested methods in the analyzed periods. Among the analyzed methods, the Transition Matrix was more accurate, with an interval of three years (until 2011) and six years. However, it should be noted that the method still has limitations of use in relation to the time between projections.